Research on the Weifang Dialect from a Lexicological Perspective (Journal of humanities and social sciences exploratio, 2025)
Weifang dialect, as an important branch of Jilu Mandarin, has a vocabulary system that is a living fossil that carries the historical culture and language life of the people in central Shandong. Based on detailed language materials, this article systematically examines the three core characteristics of Weifang dialect words from a lexical perspective: 1、Historical layering, manifested by the activation and use of a large number of homophones (such as "Zhang" and "Bai") and ancient language relics (such as "haike" and "xiaochun"), revealing the historical evolution trajectory of Chinese phonetics and semantics; 2、Cultural coding, by analyzing its unique metaphorical naming system (such as "jieliaoguier", "guanggunduochuer") and cultural vocabulary (such as "huminzi", "wuqi"), elucidates the deep coding function of dialects on regional customs and collective cognition; 3、 The autonomy of the system is reflected in its unique affix system (such as "bian" and "bu la ji"), tone changing rules, and grammaticalization phenomena (such as "qi" and "gang" as degree adverbs), which constitute an independent vocabulary grammar system distinct from modern Mandarin Chinese. Through synchronic comparison with modern Chinese, this article further reveals the differences and causes of vocabulary sources, word formation methods, semantic connotations, and pragmatic functions in Weifang dialect. Finally, the article explores the inheritance crisis and protection path of Weifang dialect vocabulary in the context of the strong promotion of Mandarin, aiming to provide typical cases for the research of Chinese dialectology and the protection of language resources.
Keywords: Weifang dialect; lexicology; Dialect comparison; Language Protection